E-Citizen at the Age of Covid-19. The Case of Opengov. Research and Results - Kalogiros, Vasileios; Tsourela, Maria (HAPSc Policy Briefs Series, 2021)
This research, in the context of ο-governance, addresses the issue of the e-citizen and e-democracy at the age of covid-19 in Greece. As it is well known, pandemic has positive effects on digitalization in government. E-gate, such as “GOV.GR”, give at the citizens the possibility to gain time and download useful documents for their work, education, travel etc. Many people at Greece visit GOV.GR and more use smartphones for entertainment, information, to visit facebook, instagram and other social media. But is the e-citizen in Greece ready for e-democracy? The page opengov.gr give the change to everyone to write their opinion about the laws and express their agreement or disagreement. After 12 years, are the Greek citizens ready for the next step…? The results of this research show that most people have a positive opinion for opengov.gr but rather prefer to write comments at mainly social media.